Language Response as a Cultural Element to Globalization - Iskandarsyah Siregar (Britain International for Academic Research (BIAR-Publisher), 2022)
Language's central and vital role and function make it very interesting to continue to be explored, questioned, and studied. The Republic of Indonesia has an official language used by its citizens, namely Bahasa Indonesia. This language aims to unite the Indonesian people who are multicultural or have ethnic and cultural diversity so that no distance separates fellow Indonesian citizens from hundreds of tribes, according to the 1928 Youth Pledge Convention. The thing that must be realized now is the use of the Indonesian language, which is getting weaker. The weakness is not that it is not used at all but that foreign terms are included in public discussion, and it tends to be considered more prestigious to be used. This study uses a descriptive qualitative method that refers to the sources of literature and the results of previous studies. The existence of Indonesian can decline when most Indonesians are happy and proud to use a foreign language that is considered more respectable and classier. However, the current condition of the existence of the Indonesian language is still in a safe stage. Bahasa Indonesia can continue to exist while preserving it by following the prevailing context and linguistic rules and developing its construction according to the needs and desires of civilization.